Mutation of the TP53 gene in acute lymphoblastic leukemia does not affect survival outcomes after haploidentical hematopoietic stem cell transplantation. Issue 5 (26th October 2022) - Zhou, Cuiyan; Zheng, Fengmei; Xu, Lanping; Zhang, Xiaohui; Chang, Yingjun; Mo, Xiaodong; Sun, Yuqian; Huang, Xiaojun; Wang, Yu
Abstract: Previous studies have demonstrated that TP53 mutation is correlated with insufficient therapy response and unfavorable prognosis in acute lymphoblastic leukemia (ALL). Few studies have investigated the impact of TP53 mutation in ALL patients after haploidentical hematopoietic stem cell transplantation (haplo‐HSCT). We completed a retrospective study of 65 ALL patients with available TP53 status who underwent haplo‐HSCT. They were divided into a TP53 mutation group (TP53 mut ) and a TP53 wild‐type (TP53 wt ) group. TP53 mut showed comparable 2‐year cumulative incidence of relapse (CIR) rates (13.1% vs 12.5%, P = .96) and 2‐year leukemia‐free survival (LFS) (74.2% vs 77.4%, P = .80) with TP53 wt . No significant differences in 2‐year overall survival (OS) rates (82.9% vs 87.3%, P = .61) or 2‐year NRM rates (12.7% vs 10.2%, P = .69) were observed in TP53 mut and TP53 wt patients. Multivariate analysis suggested that white blood cell (WBC) count at initial diagnosis (>50 × 10 9 /L: hazard ratio [HR] = 3.860, P = .016) and age (>40 years old: HR = 4.120, P = .012) are independent risk factors for 2‐year LFS. Our study showed that TP53 mutations may not be related to the unfavorable impact on survival in ALL patients after treatment with haplo‐HSCT. The present results suggested that haplo‐HSCT may eliminate the poor prognosis effect of TP53 mutation in ALL. Abstract : What's new? Mutations in tumor protein 53 (TP53), a critical regulator of cell division and tumor suppression, are correlated with unfavorable outcomes among acute lymphoblastic leukemia (ALL) patients treated with allogeneic hematopoietic stem cell transplantation (allo‐HSCT). The influence of TP53 mutation on haploidentical‐HSCT, an alternative to allo‐HSCT, remains unclear. In this retrospective study, no statistical differences in survival were observed between TP53‐mutated and TP53 wild‐type haplo‐HSCT‐treated ALL patients. By contrast, age and white blood cell count were significant independent risk factors for two‐year disease‐free survival. The findings suggest that haplo‐HSCT potentially eliminates deleterious prognostic impacts linked to TP53 mutation in ALL.